Spin density localization and accessibility of organic radicals affect liquid-state DNP efficiency. Issue 8 (18th February 2021) - Levien, Marcel; Reinhard, Maik; Hiller, Markus; Tkach, Igor; Bennati, Marina; Orlando, Tomas
Abstract : Scalar liquid DNP performance scales of a factor ∼5 depending on the spin density distribution and accessibility of the radical. Abstract : We report a large variation in liquid DNP performance of up to a factor of about five in coupling factor among organic radicals commonly used as polarizing agents. A comparative study of 1 H and 13 C DNP in model systems shows the impact of the spin density distribution and accessibility of the radical site by the target molecule.